2014
DOI: 10.1073/pnas.1320753111
|View full text |Cite
|
Sign up to set email alerts
|

Circulating hematopoietic stem and progenitor cells are myeloid-biased in cancer patients

Abstract: Cancer is associated with a profound perturbation in myelopoiesis that results in the accumulation of myeloid-derived suppressor cells (MDSCs) to promote disease progression. Recent studies in mice suggest that tumor-derived factors could regulate the differentiation of hematopoietic stem and progenitor cells (HSPCs) in the bone marrow and subsequently contribute to dysregulation of hematopoiesis. However, the nature and role of HPSCs in patients with cancer remain unknown. Here we show, in detailed studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
203
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(211 citation statements)
references
References 34 publications
(48 reference statements)
7
203
0
1
Order By: Relevance
“…However, the detailed mechanisms of this effect in humans remain elusive. In a recent study, Wu and colleagues confirmed the role of GM-CSF and IL6 during the expansion of MDSCs from human CD34 þ hematopoietic progenitor cells (46). Utilizing murine bone marrow cells, human CD34 þ hematopoietic progenitor cells and a human monocyte-neuroblastoma coculture model, we provided insightful results emphasizing the key contribution of the M-CSF/CSF-1R pathway during the induction of MDSCs and TAMs.…”
Section: Discussionsupporting
confidence: 52%
“…However, the detailed mechanisms of this effect in humans remain elusive. In a recent study, Wu and colleagues confirmed the role of GM-CSF and IL6 during the expansion of MDSCs from human CD34 þ hematopoietic progenitor cells (46). Utilizing murine bone marrow cells, human CD34 þ hematopoietic progenitor cells and a human monocyte-neuroblastoma coculture model, we provided insightful results emphasizing the key contribution of the M-CSF/CSF-1R pathway during the induction of MDSCs and TAMs.…”
Section: Discussionsupporting
confidence: 52%
“…Meanwhile, immune effector cells not only produce large amounts of inflammatory cytokines to alleviate immune damage caused by anticancer drugs and enhance the immunosurveillance capabilities of patients with cancer, 37 but additionally eliminate potential or residual tumor cells after chemotherapy, including even drug-resistant tumor cells and putative cancer stem cells. [38][39][40] Secondly, alternate application of CIK and NK cells exhibits a synergistic antitumor immunity via different mechanisms compared to the CIT with only CIK cells, which was also found by Maniar et al and Cui et al 34,35 On the other hand, it was reported that the circulating hematopoietic stem and progenitor cells from various patients with solid cancers exhibited a generalized myeloid bias with a skew toward granulocytic differentiation, 41 which increased the neutrophil-to-lymphocyte ratio (NLR), a poor prognostic indicator. 42 Adjuvant CIT could reverse the NLR, resulting in immune equilibrium to reduce tumor recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 69%
“…Expansion of these early BM compartments by G-CSF could provide a constant supply of lineage-committed progenitors during tumor-induced production of Ly6G + neutrophils. This would also explain the increased number of granulocytemacrophage colony-forming units observed in BM of HER2 transgenic BALB/c tumor-bearing mice (49), and the increased numbers of circulating HSPCs observed in the blood of human patients with different types of carcinomas that also show elevated G-CSF levels (50). The pleiotropic mechanisms by which G-CSF regulates myeloid progenitor differentiation and proliferation (51), apoptosis of mature neutrophils (52), and priming of neutrophil activation (53), together with our previously unidentified observations of expansion of HSCs and MPPs, support the hypothesis that pathways involved in immune activation are also linked to early hematopoiesis to fulfill the demand of the immune system (35).…”
Section: Discussionmentioning
confidence: 98%
“…Skewing of HSPC differentiation toward the myeloid lineage has been reported in mouse models (30,49) and in human patients (50) with different types of solid tumors, but until now the mechanism responsible was not known. Our data demonstrate a previously unidentified mechanism for the production of T cell-suppressive neutrophils in which early compartments of the hematopoietic hierarchy in BM are regulated by tumor-derived G-CSF.…”
Section: Discussionmentioning
confidence: 99%